Multiomic analysis identifies CPT1A as a potential therapeutic target in platinum-refractory, high-grade serous ovarian cancer - Dongqing Huang; Shrabanti Chowdhury; Hong Wang; Sara R. Savage; Richard G. Ivey; Jacob J. Kennedy; Jeffrey R. Whiteaker; Chenwei Lin; Xiaonan Hou; Ann L. Oberg; Melissa C. Larson; Najmeh Eskandari; et al. (2021)
Resistance to platinum compounds is a major determinant of patient survival in high-grade serous ovarian cancer (HGSOC). To understand mechanisms of platinum resistance and identify potential therapeutic targets in resistant HGSOC, we generated a data resource composed of dynamic (±carboplatin) protein, post-translational modification, and RNA sequencing (RNA-seq) profiles from intra-patient cell line pairs derived from 3 HGSOC patients before and after acquiring platinum resistance. These profiles reveal extensive responses to carboplatin that differ between sensitive and resistant cells. Higher fatty acid oxidation (FAO) pathway expression is associated with platinum resistance, and both pharmacologic inhibition and CRISPR knockout of